Perspectives on Quality of Life in Chronic Eye Disease: Diabetic Retinopathy as a Model - nimour, baya (Journal of Social Sciences and Humanities, 2023)
Globally, chronic eye diseases (diabetic retinopathy, glaucoma, cataracts and age-related macular degeneration) are increasing. In Algeria, they are a priority for public health and represent the main cause of blindness if the diagnosis is not early. Research and studies have attempted to determine the predictive factors of the development and progression of these diseases, which have a psychological, social and quality of life impact. Besides the disease itself, the treatment and its consequences are determinants of the quality of life and are essential elements to consider during prolonged treatment. Diabetic retinopathy is the main cause of visual impairment, which affects the quality of life. In this article, we present the perspectives and influences of chronic eye disease on quality of life, while presenting diabetic retinopathy as a model.